2022
DOI: 10.1002/maco.202213339
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behavior of additively manufactured AISI 316L stainless steel under atmospheric conditions

Abstract: This study investigated the corrosion behavior of AISI 316L produced by direct energy deposition (DED). Microstructural and chemical analysis showed a homogeneous distribution of Si and Si-Mn inclusions of 0.5-1 µm and the Cr and Mo enrichment within interdendritic areas. Scanning Kelvin probe analysis of additively manufactured stainless steel highlighted a regular "striped-like" surface potential feature with a potential gradient of 30 mV for a mean value of 0.320 ± 0.017 V versus standard hydrogen electrode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Most of these studies have tried to establish a link between the fabrication parameters of selective laser melting (SLM), laser-engineered mesh forming (LENS), and DED and the mechanical properties of building materials [7,10]. In some studies, it has been reported that the microstructure regularity and the increase in the time interval between successive layers positively affect the mechanical properties due to an increase in the cooling rate [6,12]. However, very little work has been conducted on the effects of the re-melting process during the production of 316L material through the DED method [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies have tried to establish a link between the fabrication parameters of selective laser melting (SLM), laser-engineered mesh forming (LENS), and DED and the mechanical properties of building materials [7,10]. In some studies, it has been reported that the microstructure regularity and the increase in the time interval between successive layers positively affect the mechanical properties due to an increase in the cooling rate [6,12]. However, very little work has been conducted on the effects of the re-melting process during the production of 316L material through the DED method [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Stainless steel is widely used in aerospace, automobile, mobile communication, medical equipment, and architecture due to its excellent formability, corrosion resistance, compatibility, and toughness. [1][2][3][4][5] However, when stainless steel is exposed to a corrosive environment for a long time, its performance can be significantly reduced. [6,7] Because problems of pickling pollutants, uneven passivation regions, and serious environmental pollution have been discovered in the pickling passivation of stainless steel, this process does not meet the process requirements of green cleaning.…”
Section: Introductionmentioning
confidence: 99%